An experimental study on microstructural characteristics and mechanical properties of stainless-steel 316L parts using directed energy deposition (DED) process - Kim, Jung Sub; Kang, Byoung Joo; Lee, Sang Won (Journal of mechanical science and technology, 2019)
We investigated the microstructural characteristics and mechanical properties of stainless-steel 316L parts fabricated by directed energy deposition (DED) process, which is one of the additive manufacturing (AM) technologies. In this research, the 316L parts were fabricated by DED process by varying three process parameters: Laser power, scanning speed and mass flow rate of powder. A total of eight experimental cases were sorted out, and the DED parts from each experimental case were characterized in views of composition, defects, geometrical height, micro-hardness, friction and modulus. The analysis showed that the mechanical properties–micro-hardness, friction and modulus–of the 316L parts can be maximized in the case of the low laser power (400 W), high scanning speed (10 mm/s) and low mass flow rate of powder (10 g/min). In addition, the defects such as blowholes and cracks can be minimized under the condition of the low laser power (400 W) and low mass flow rate (10 g/min), respectively.